How do public librarians constitute information literacy?. (June 2019) - Demasson, Andrew; Partridge, Helen; Bruce, Christine
The public library has historically been entrusted with the design and delivery of services and programmes aimed at supporting the information literacy needs of the community-at-large. However, despite that central role little research has been devoted to understanding the ways in which public librarians, the conduit between the programme and the public, constitute the very concept (information literacy) they are delivering. This study has sought to redress that inequity by way of a phenomenographic study into the ways in which public librarians constitute information literacy. Data was collected via 20 semi-structured, one-on-one interviews with public librarians working in Queensland, Australia. The study revealed that the respondents constituted information literacy in four ways, as: intellectual process, technical skills, navigating the social world and gaining the desired result. Those findings and the attending study will help to provide a new evidence base that assists in the design and delivery of activities supporting future information literacy endeavors in the nation's public libraries.